EVALUATION OF IMMUNOMODULATORY ACTIVITY OF SESBANIA GRANDIFLORA FLOWERS EXTRACT IN MICE - Mallik Arunabha; Nayak Satish (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
The aim of the present study was to investigate the immunomodulatory activity of Sesbania grandiflora on cellular and humoral immunity. Oral administration of the methanolic extract (200 and 400mg/kg) of S. grandiflora flowers, in mice, dose-dependently significantly enhanced the production of circulating antibody titre in mice in response to SRBC. It significantly potentiated the delayed-type hypersensitivity reaction induced by sheep red blood cells (SRBC). Good response was also found towards phagocytosis in carbon clearance assay and prevented myelosuppression in cyclophosphamide drug. Aqueous extract at 250mg/kg dose level failed to show immunomodulatory activity but 500mg/kg of aqueous extract potentiated the activity however less significantly compared with both dose of methanolic extract. The results obtained in this study indicate that methanolic extract (400mg/kg) of S. grandiflora possesses potential immunomodulatory activity.